Assessment of mathematical competence among primary students in the city of Berehovo - Pallay Katalin; Поллоі Каталін; Bodnár Alexandra; Боднар Олександра (Видавництво «Код», 2025)
Abstract. The quality of public education is largely determined by the effectiveness of the teaching and learning processes, which is closely related to internal and external evaluation systems. Competence assessments contribute significantly to evaluating education systems, tracking learning outcomes, and identifying their strengths and weaknesses. This paper presents a competence assessment study conducted among Hungarian-speaking students in Berehove, Ukraine. The research specifically examines the competencies of fourth-grade students in logical-mathematical tasks. According to our results, the parents’ educational background and the father’s employment abroad significantly influence students’ achievements. The competence measurement of Hungarian students in Transcarpathia provides insights into the effectiveness of the «New Ukrainian School» educational reform and may contribute to the further development of local educational practices. In our research, we conducted an assessment of reading comprehension, mathematical, and science competencies among fourth-grade students from Hungarian-language schools in Berehove, focusing specifically on how various sociodemographic factors influence academic achievement. Particular emphasis was placed on identifying how parental educational attainment, preschool education, parental involvement, private tutoring, and fathers’ employment status (including working abroad) affect student performance. In addition to bivariate analyses, we applied multivariate regression models to evaluate these influences more comprehensively. Our findings confirmed our first two hypotheses, indicating that both preschool education and parental educational attainment significantly affect students’ performance. Active parental involvement, such as helping with homework and regularly discussing school activities, was also positively associated with better academic outcomes.

Резюме. Якість загальної середньої освіти значною мірою визначається ефективністю навчально-виховного процесу, яка тісно пов’язана із системою внутрішнього та зовнішнього оцінювання. Оцінювання компетентностей сприяє моніторингу якості освітньої системи, дає змогу відстежувати навчальні досягнення учнів та виявляти сильні й слабкі сторони освіти. У статті представлено результати дослідження рівня компетентностей учнів четвертих класів угорськомовних шкіл міста Берегове.
Оцінювання математичної компетентності серед учнів початкових класів у місті Берегово
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00015727 Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-13
Keywords: assessment; mathematical competence; elementary school students